We have 2x-6=4x+4

Taking x one side and constant another side ,so we have

2x-4x=4+6

-2x=10

(-2x)/(-2)=10/(-2)

x=-5

QED

2x - 6 = 4x + 4

To solve for x you need to separate the variable terms from the constant terms. Subtract 4x

2x - 6 - 4x = 4

Add 6

2x - 4x = 4 + 6

Simplify both sides

-2x = 10

Solve for x by dividing by -2

x = -5

Solve for x

2x-6=4x+4

Move all the variables on one side

-6-4=4x-2x

Simplify

-10=2x

Divide

x=-5

To solve this equ:

- Rewrite: 2x-6=4x+4
- Start combining like terms, subtract 2x from both sides: -6=2x+4
- Isolate the variable using the opposite operation of addition (subtraction): -10=2x
- 2x is multiplication, so what is the opposite operation for that? (division) -- Divide 2 on both sides:` `
- Simplify: -5=x, or
**x=-5**

2x - 6 = 4x + 4

To solve this equation , first we have to get the " x " variables on all the same side. In order to do that , subtract 4x on both sides . By subtracting 4x on both sides , you should get

-2x - 6 = 4 now add 6 on both sides

By adding 6 on both sides , you should get

-2x = 10 now we have to get " x " alone . In order to get " x " alone , divide by -2 on both sides .

By dividing by -2 on both sides , you should get

x = -5 which is your answer

2x-6=4x+4 (original equation)

-6=2x+4 (subract the 2x on both sides)

-10=2x (subtract the 4 on both sides)

-5=x (divide by two on both sides)

The first step is to subract the 2x to the other side. The second step is to subtract the 4. Then you divide by two. You need to get the number on one side, while the variable is on the other.